CAUDAL NEUROSECRETORY SYSTEM OF FOUR HILL STREAM FISHES OF INDIA - Tiwari, S.; Gopesh, A.; Shah, K.; Srivastava, P. (Journal of Indian Fisheries Association, 2010)
Caudal neurosecretory system is an additional neuroendocrine system found in fishes. Great variation has been observed among different groups of fishes, so far its organization is concerned. Much work has been undertaken on the caudal neurosecretory system of elasmobranchs and teleosts. Large size scattered Dahlgren cells in the posterior end of spinal cord, corresponding to last few vertebrae, with long running axon process and a neurohaemal organ the urophysis are the characteristic features of the system. Although thoroughly investigated in fresh water carps, no work is reported in hill-stream fishes. In an attempt to investigate structure and organization of caudal neurosecretory system in hill-stream fishes, present investigation was undertaken in four hill-stream fish of Indian freshwater namely, Barilius bendelensis, Garra gotyla, Schizothorax plagiostomus and Tor tor. The organization of this system in hill-stream fishes was found to be quite different from that observed in fresh water carps. It displays an organization which is more close to the organization of caudal neurosecretory system observed in elasmobranchs. The features are described and discussed.Key words: Caudal neurosecertory system, Carps, Hill-stream, Urophysis and neuroendocrine system. Â